GWAS analysis reveals candidate genes associated with density tolerance (ear leaf structure) in maize (Zea mays L.) - Chunxiang Li; Yongfeng Song; Yong Zhu; Mengna Cao; Xiao Han; Jinsheng Fan; Zhichao Lü; Yan Xu; Yu Zhou; Xing Zeng; Lin Zhang; Ling Dong; et al. (Journal of Integrative Agriculture, 2025)
Planting density is a major limiting factor for maize yield, and breeding for density tolerance has become an urgent issue. The leaf structure of the maize ear leaf is the main factor that restricts planting density and yield components. In this study, a natural population of 201 maize inbred lines was used for genome-wide association analysis, which identified nine SNPs on chromosomes 2, 5, 8, 9, and 10 that were significantly associated with ear leaf type structure. Further verification through qRT-PCR confirmed the association of five candidate genes with these SNPs, with the Zm00001d008651 gene showing significant differential expression in the compact and flat maize inbred lines. Enrichment analysis using the Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) databases suggested that this gene is involved in the glycolysis process. An analysis of the basic properties of this gene revealed that it encodes a stable, basic protein consisting of 593 amino acids with some hydrophobic properties. The promoter region contains stress and hormone (abscisic acid (ABA)) related elements. The mutant of this gene increased the first ear leaf angle (eLA) and leaf angle of the first leaf below the first ear (bLA) by 4.96 and 0.97°, respectively, compared with normal inbred lines. Overall, this research sheds light on the regulatory mechanism of ear and leaf structures that influence density tolerance and provides solid foundational work for the development of new varieties.